Karakteristik Marshall Campuran Asphalt Concrete Binder Course (AC-BC) Yang Mengandung Cangkang Kelapa Sawit Sebagai Agregat Kasar - Alli, Syaifullah; Mukhlis, Mukhlis; Lusyana, Lusyana; Adibroto, Fauna; Suardi, Enita (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2019)
AC-BC coating is one type of hot mix asphalt with a minimum thickness of 4 cm. The most important characteristic of this mixture is the stability of the surface layer where the surface layer must be able to accept all types of work loads. As a foundation layer, the asphalt content it contains must be sufficient so that it can provide a waterproof coating. The aggregate used is rather rough compared to the surface wear layer. The aggregate requirement that dominates in the asphalt mixture makes us research what materials can be used as a mixture in the asphalt mixture. Palm oil waste provides an alternative opportunity as a material making up the asphalt mixture. The intended waste is oil palm shell which can be used as a substitute for coarse aggregate in asphalt mixture. The purpose of this study is to obtain the ACO BC mix KAO calculation without using an oil palm shell and using a palm oil shell with variations of 2.5%, 5%, 7.5%, 10%, 12.5%, and 15% as substitution of coarse aggregate and know the effect of adding palm shells to the mixture of test specimens on Marshall parameter values. Before the manufacture of test specimens, the materials are tested in advance in accordance with the 2010 Revised 3 General Specifications. 3. The addition of oil palm shells to the asphalt mixture showed an increase in KAO value. Based on the results of the study, the oil palm shell was suitable as an additive to the Asphalt Concrete-Binder Course (AC-BC) mixture because it met the requirements of the 2010 Revised 3 General Bina Marga General Specifications.Keywords: mixture of AC-BC, oil palm shells, KAO, Marshall parameters